Relationship of the clinical characteristics of rheumatoid arthritis to work capacity and efficiency - O Yu Vakulenko; O A Krichevskaya; D V Goryachev; Sh F Erdes (Научно-практическая ревматология, 2012)
Objective: to study the impact of the clinical characteristics of rheumatoid arthritis (RA) on work efficiency. Subjects and methods. One hundred and thirty-seven patients (116 women and 21 men) with RA were examined. Their mean age was 52.03+13.17 years; mean age at disease onset was 42.12+14.43 years. Median RA duration was 84 (range 24-174) months. DAS 28 for RA was moderate. The HAQ score was 1.42+0.82. Results. Fifty-nine (43%) of the 137 patients were in work. Absenteeism was 28.2%. It was equal to 0 in 28 of the 59 working subjects. The mean presenteeism was 42.3±27.9%. The reduction of overall work efficiency was 54.8±34.4%. The day-to-day activity determined in all the patients was reduced by 53.6±25.7%. Absenteeism turned out to be negatively related to RA duration (R = 0.26). DAS 28 scores were directly related to all WPAI indicators: absenteeism (R = 0.28), presenteeism (R = 0.63), lower overall work efficiency (R = 0.47), day-to-day activity (R = 0.64). The WPAI indicators (R >0.5), exclusive of absenteeism, were noted to have the strongest correlation with VAS pain intensity. The HAQ score was unassociated with absenteeism, but its association with presenteeism, lower overall work efficiency, and day-to-day activity proved to be high (R = 0.65; R = 0.43; R = 0.75, respectively). The correlation of the WPAI components with the transformed index of a patient's physical state (SF-36 PCS) was much higher than that with mental one (MCS). Conclusion. RA activity had a major influence on work efficiency. Presenteeism was much stronger related to the clinical characteristics of RA than with absenteeism. All WPAI scores were associated with activity, degree of functional defect, quality-of-life values, and fatigability. At the same time, absenteeism was least related to the clinical characteristics of RA.